Development and systematic oxidative stress of a rat model of chronic bronchitis and emphysema induced by biomass smoke. (1st August 2013) - Hu, Guoping; Zhou, Yumin; Hong, Wei; Tian, Jia; Hu, Jinxing; Peng, Gongyong; Cui, Jiangyu; Li, Bing; Ran, Pixin
ABSTRACT: Background : Epidemiological research and meta-analyses of published data have shown that biomass smoke (BS) is a risk factor for chronic obstructive pulmonary disease (COPD). However, the link between BS and COPD lacks experimental confirmation. Objectives : To verify whether BS can induce pathologic changes and systemic oxidative stress, which may be relevant to the development of emphysema and chronic bronchitis in rats. Methods : Rats were exposed to BS, cigarette smoke (CS), or clean air (sham) for 14 weeks. During the exposure, the O2, SO2, and CO levels were monitored. Pathological changes in the lungs, systemic oxidative stress, and inflammation biomarkers, together with GSTM1 and GSTP1 mRNA expression in the lung were measured. The glutamate–cysteine ligase catalytic subunit (GCLC) protein expression in the lung was measured using immunohistochemistry and western blotting. Results : The O2, CO, and SO2 levels were 20.31 ± 0.03%, 981.72 ± 64.76, and 2.59 ± 0.26 mg/m 3 for the BS group, respectively, while their levels in the CS group were 20.28 ± 0.15%, 745.56 ± 30.83, and 12.64 ± 0.591 mg/m 3 respectively. As with the rats exposed to CS, the BS rats showed an increased number of inflammatory cells in the bronchoalveolar lavage fluid, an increased pulmonary mean linear intercept and a decreased pulmonary mean alveolar number. Characteristics of chronic bronchitis and peribronchial fibrosis were also found in the BS-exposed rat lungs. Reduced body weight, systemic oxidative stress, and increased GCLC protein expression in the lungs were observed in the rats exposed to BS and CS. Conclusions : BS can cause emphysema and chronic bronchitis similar to that caused by CS, which is accompanied by systemic oxidative stress and inflammation.